The Philosophical Meaning of the Author’s Myth: Evolution of the Archetypal Image of a Religious Visionary in the Dramatic Works of Lesya Ukrainka - Bodyk, Ostap; Fedorova, Yuliya; Horodniuk, Nataliia (2022)
The article traces and analyses the movement of the author’s consciousness of Lesya Ukrainka in solving the research issue of evolution of the archetypal image of a religious visionary in the dramatic works of Ukrainian poetess through the prism of mythopoetic archetypal categories on different “sections” of her dramatic sketches Vavylons’kyj polon (Babylonian Captivity), Na rujinaсh (On the Ruins) and poems Kassandra (Cassandra) and Orhija (The Orgy). The author explains that, referring the ancient subjects, Lesia Ukrainka realizes the need to breathe new life into the mythology of the ancients, look at the history of humankind as a tragic process of the struggle between good and evil, connect the movement of history with manifestations of spiritual stability, with its tendency to the ideals of good. According to her aesthetic views in the artistic perception of antiquity, the poetess does not seek to aestheticize it, but to reveal in the ancient myth the eternal, timeless psychological state of human inner life and in this way explore the “catastrophes” of the modern soul.
Keywords: author’s myth; phenomenon of prophetism; religious prophecy; archetypal and mythological structure; dramatic sketches and poems; existential dilemma in national issue